Meet the collection 30th anniversary of the Yokohama Museum of Art = Āto to hito to, bijutsukan - Osaka, Eriko (Torch Press, 2019)
On the occasion of its 30th anniversary, the Yokohama Museum of Art celebrates this milestone with the exhibition 'Meet the Collection', which comprises around 350 works selected from its diverse collection of modern and contemporary art. The exhibition is designed with two main subthemes in mind Life and World and features guest artists Tabaimo, Asai Yusuke, Imazu Kei, and Suga Kishio. Working with the curatorial team, these four artists combined their own works with those from the museum collection, reinterpreting it and reconfiguring the galleries with new perspectives. This catalogue gives an inside look at the seminal exhibition and its artworks.
Impressum: This publication is published in connection with following exhibition: "30th Anniversary of the Yokohama Museum of Art: Meet the Collection", April 13 - June 23, 20219, Yokohama Museum of Art
Keywords: Yokohama-Bijutsukan; Sammlung; Kunst; Japan; Art, Japanese / Exhibitions; Yokohama Bijutsukan / Exhibitions; Yokohama Bijutsukan; Art, Japanese; Bijutsu-Zushū; Catalogs; Exhibition catalogs; Ausstellungskatalog -- Yokohama-Bijutsukan -- 13.04.2019-23.06.2019 -- Yokohama; Festschrift